Newspaper Analysis - Dietrichson, Aleksander (2018)
Our team is currently working on a suite of products to provide media analytics to e.g. political campaigns. As part of this project we perform some analyses of traditional media including online newspapers to obtain differents metrics (theme of day, relation candidates-daily themes, repercussion of announcements, relations between candidates, importance of candidates in the daily news, etc) that will be used by the political analysts of a campaign.